2021
DOI: 10.1097/txd.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Pretransplant Educational Intervention in Kidney Patients

Abstract: Kidney TransplantationBackground. Poor patient knowledge about transplantation is a significant problem following kidney transplant. A video-based educational intervention was developed to supplement standard education provided by transplant teams. Methods. A multicenter randomized controlled trial tested the intervention delivered to patients undergoing assessment or waitlisted for kidney transplant. Adult participants were randomized to the control (standard education) or the intervention group, consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Although our findings of gains in several transplant‐pursuit indicators are promising, they require validation compared to a control group. In a recent randomized controlled trial conducted at 3 Canadian sites, animation mixed with live action yielded significant knowledge increases, but did not impact self‐efficacy, quality of life, or medication beliefs relative to usual care among transplant candidates 24 . The authors attributed this to a “one‐size fits all” video delivery strategy and suggested tailoring and a multicomponent intervention approach to improve these outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our findings of gains in several transplant‐pursuit indicators are promising, they require validation compared to a control group. In a recent randomized controlled trial conducted at 3 Canadian sites, animation mixed with live action yielded significant knowledge increases, but did not impact self‐efficacy, quality of life, or medication beliefs relative to usual care among transplant candidates 24 . The authors attributed this to a “one‐size fits all” video delivery strategy and suggested tailoring and a multicomponent intervention approach to improve these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…elements, which reduces cognitive load and enhances information processing, as suggested by Mayer's cognitive theory of multimedia learning. 23 Other studies have also reported significant knowledge increases using standalone animation 13 or blended animation and live action 24 in transplantation and other health contexts. 25 Our report's 21% knowledge gain with a r = .54 effect size is considered large and promising and is similar to a meta-analysis of standalone animated video education in different healthcare contexts that found a small to medium effect size (Cohen's d = .38) across 20 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cronbach's alpha of the tool is 0.79 to 0.88, and the intragroup correlation coefficient is 0.76 to 0.94, which has good reliability. At present, it is applied in the United States (Bruns et al, 2021 ), South Korea (Kang & Jeong, 2020 ), North American countries (Mansell et al, 2019 ), Canada (Mansell et al, 2021 ) and Iran (Ganjali et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our interdisciplinary team collaborated with Lung Saskatchewan and patient stakeholders to develop a 6-part video series that describes the lung transplant process. The English videos, which were adapted from previous work [3][4][5] according to best practice for education for patients pursuing transplants, 6 are intended to supplement the first education session provided by the transplant respirologist. This initial meeting includes basic information about the transplant process (eg, what a lung transplant is, the process involved, potential risks and benefits, and what the expectations are before and after the transplant).…”
mentioning
confidence: 99%